Pengembangan Modul Pembelajaran Ips Berbasis Kearifan Lokal Uma Lengge Untuk Meningkatkan Literasi Budaya Siswa Sekolah Dasar - Runi Hartati; Rusmawan Rusmawan (Publikasi Berkala Pendidikan Ilmu Sosial, 2024)
This research is motivated by the need for a local wisdom Uma Lengge social studies learning module that can improve Cultural Literacy for fifth grade elementary school students. This article was written with the aim of developing a local wisdom Uma Lengge-based social studies learning module to improve Cultural Literacy for fifth grade elementary school students. The type of research used in this study is Research and Development (R&D). The research was conducted involving three validators, two elementary school teachers for needs analysis, and 23 students who were subjects in the trial process of the local wisdom Uma Lengge-based social studies learning module to improve Cultural Literacy. Observation, interviews and document studies are data collection techniques used in the study. Data analysis uses quantitative analysis and qualitative analysis. The results of the study are (1) The ADDIE development model is used in the development of a local wisdom Uma Lengge-based social studies learning module to improve Cultural Literacy for fifth grade elementary school students. (2) The quality of the IPS module with a Likert scale of 1-4 is included in the criteria of "Already Suitable" and the average score is 3.30 which is included in the category "No Revision Required" (3) The results of the implementation of the IPS module, the average score is 51.5 before using the module, the average score is 87.3 after using the module, the overall percentage increase in module use is 59% with the category "High".